High-flame-retardant insulating power cable
By adopting a combined structure of tinned copper wire, mica tape, glass fiber wire, polyvinyl chloride and modified resin in the power cable, the cable has poor flame retardant effect and harmful gas emissions under flame conditions, and an efficient and environmentally friendly flame retardant effect is achieved.
Patent Information
- Application Number
- CN202510060798.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-01-15
AI Technical Summary
Existing power cables have poor flame retardant effects under flame conditions, dripping during combustion, causing fire to spread, and halogen-containing materials are harmful to the environment and human health.
Using a highly flame retardant insulated power cable structure composed of tinned copper wire, mica tape, glass fiber wire, polyvinyl chloride and modified resin, the modified resin is prepared through a multi-step reaction, including functionalized carbon nanotubes and reinforced fillers, forming a multi-layer protective layer to block oxygen and heat.
It significantly improves the flame retardant effect of the cable, avoids the generation of drips, reduces the emission of harmful gases, and the preparation process of the modified resin is environmentally friendly and efficient.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame-retardant cable material preparation, in particular to a highly flame-retardant insulated power cable. Background Art
[0002] Power cables are cables used to transmit and distribute electrical energy. They are commonly used in urban underground power grids, power station lead-out lines, internal power supply for industrial and mining enterprises, and underwater transmission lines across rivers and seas. In power lines, the proportion of cables is gradually increasing. Power cables are cable products used to transmit and distribute high-power electrical energy in the trunk lines of power systems, including 1-500KV and above various voltage levels, and various insulated power cables. Traditional flame-retardant power cables improve the flame retardancy of cables by adding halogen-containing or non-halogen-containing flame retardants. Although it can significantly improve the performance of cables under flame conditions, there are problems such as large smoke generation, serious harmful gas emissions, and rapid aging and deterioration. In addition, halogen-containing materials may produce highly toxic acidic gases when dissolved in water, which has a great impact on the environment and human health. Therefore, the development of new environmentally friendly and efficient flame-retardant power cables has become a technical problem that needs to be solved urgently. Summary of the invention
[0003] The purpose of the present invention is to provide a highly flame-retardant insulated power cable, which solves the problem that the current power cable has poor flame-retardant effect and drips when burning, thereby causing the fire to spread.
[0004] The purpose of the present invention can be achieved by the following technical solutions: A highly flame-retardant insulated power cable, comprising a plurality of conductors arranged in sequence from the inside to the outside, wherein the surface of the conductor is coated with an insulating layer, a wrapped inner lining layer is arranged outside the insulating layer, a filler is filled between the wrapped inner lining layer and the insulating layer, a protective layer is coated outside the wrapped inner lining layer, and a sheath is coated outside the protective layer; The conductor is a tinned copper wire, the inner lining layer of the wrapping is a mica tape, the filler is glass fiber yarn, the insulating layer and the protective layer are polyvinyl chloride, and the sheath is prepared from modified resin.
[0005] Further, the modified resin is prepared by the following steps: Step A1: 4-maleimidophenol, potassium carbonate and DMF are mixed evenly, nitrogen is introduced for protection, and the mixture is reacted for 10-15 minutes at a speed of 120-150 r / min and a temperature of 50-60° C., and then 3-chloropropyltriethoxysilane is added and reacted for 1-1.5 hours to obtain a modifier, and carboxyl carbon nanotubes, dicyclohexylcarbodiimide, KH550 and toluene are mixed evenly, and the mixture is reacted for 3-5 hours at a speed of 200-300 r / min and a temperature of 20-25° C. to obtain pretreated carbon nanotubes; Step A2: dispersing the pretreated carbon nanotubes in ethanol, stirring and adding KH550, a modifier and deionized water at a speed of 200-300 r / min and a temperature of 60-70° C., reacting for 3-5 hours to obtain modified carbon nanotubes, and uniformly mixing the modified carbon nanotubes, 4-formylphenylboronic acid and n-hexane, reacting for 5-10 minutes at a speed of 60-80 r / min and a temperature of 70-75° C. to obtain functionalized carbon nanotubes; Step A3: The reinforcing filler, functionalized carbon nanotubes, 1,4-phenylenediboric acid and toluene are mixed, stirred for 6-8 hours at a rotation speed of 600-800 r / min and a temperature of 70-80°C to obtain a composite filler, and the SBS masterbatch, PP masterbatch, composite filler, diisopropylbenzene peroxide and xylene are mixed evenly, reacted for 2-2.5 hours at a rotation speed of 60-80 r / min and a temperature of 130-135°C, cooled to room temperature, filtered to remove the filtrate, and melt-extruded the filter cake to obtain a modified resin.
[0006] Furthermore, the molar ratio of 4-maleimidophenol, potassium carbonate and 3-chloropropyltriethoxysilane in step A1 is 1:1.1:1, and the molar ratio of carboxyl groups on carboxyl carbon nanotubes, dicyclohexylcarbodiimide and KH550 is 1:1:1.
[0007] Furthermore, the amount ratio of the pretreated carbon nanotubes, ethanol, KH550, modifier and deionized water in step A2 is 1 g:15 mL:30 mg:30 mg:3 mL, and the molar ratio of the amino groups on the modified carbon nanotubes to 4-formylphenylboronic acid is 1:1.
[0008] Furthermore, the mass ratio of the reinforcing filler, functionalized carbon nanotubes and 1,4-phenylenediboric acid described in step A3 is 1:3:3, and the weight ratio of SBS masterbatch, PP masterbatch, composite filler and dicumyl peroxide is 40-60:130-150:35-55:3-8.
[0009] Furthermore, the reinforcing filler is prepared by the following steps: Step B1: octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(aminopropyl)tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the mixture is reacted for 3-5 hours at a speed of 120-150 r / min and a temperature of 105-110° C. to obtain bisaminopolysiloxane; bisaminopolysiloxane, 4-vinylbenzaldehyde, sodium carbonate and DMF are mixed uniformly, and the mixture is reacted for 5-7 hours at a speed of 150-200 r / min and a temperature of 80-90° C. to obtain a modified monomer; Step B2: Sodium dodecylbenzene sulfonate, styrene, acrylonitrile, modified monomer and DMF are mixed uniformly, and potassium persulfate and polytetrafluoroethylene emulsion are added under the conditions of a rotation speed of 200-300 r / min and a temperature of 80-85° C., and the reaction is carried out for 2-3 hours, and the temperature is raised to 90-95° C., and the reaction is continued for 3-5 hours to obtain a composite liquid, and the composite liquid and sulfuric acid solution are mixed uniformly, and the sulfuric acid solution is added under the conditions of a rotation speed of 600-800 r / min and a temperature of 90-95° C., and the stirring is carried out for 1-1.5 hours, and the filtrate is filtered to remove the filtrate to obtain a precursor; Step B3: Mix the precursor, DOPO and ethanol evenly, and reflux for reaction at a speed of 60-80 r / min and a temperature of 78-80°C for 3-5 hours to obtain a modified precursor; mix the modified precursor, 4-vinylbenzeneboronic acid, chloroplatinic acid and n-hexane evenly, and react for reaction at a speed of 120-150 r / min and a temperature of 80-85°C for 2-4 hours to obtain a reinforced filler.
[0010] Furthermore, the molar ratio of octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(aminopropyl)tetramethyldisiloxane described in step B1 is 1.4:1:3:2, the molar ratio of bisaminopolysiloxane and 4-vinylbenzaldehyde is 1:2, and the amount of sodium carbonate used is 1% by mass of 4-vinylbenzaldehyde.
[0011] Furthermore, the mass ratio of sodium dodecylbenzene sulfonate, styrene, acrylonitrile, modified monomer and DMF, potassium persulfate and polytetrafluoroethylene emulsion described in step B2 is 0.8:45:12:15:200:0.3:20, the solid content of polytetrafluoroethylene emulsion is 60%, the mass ratio of the composite liquid and sulfuric acid solution is 2:5, and the mass fraction of the sulfuric acid solution is 5%.
[0012] Furthermore, the amount ratio of the precursor, DOPO and ethanol described in step B3 is 1g:1.5g:15mL, the molar ratio of the Si-H bond on the modified precursor and 4-vinylbenzeneboronic acid is 1:1, and the amount of chloroplatinic acid is 1‰ of the mass of 4-vinylbenzeneboronic acid.
[0013] Beneficial effects of the invention: A highly flame-retardant insulated power cable disclosed in the invention comprises a plurality of conductors arranged in sequence from the inside to the outside, wherein the surface of the conductor is coated with an insulating layer, a wrapped inner lining layer is arranged outside the insulating layer, a filler is filled between the wrapped inner lining layer and the insulating layer, a protective layer is coated outside the wrapped inner lining layer, a sheath is coated outside the protective layer, and the sheath is prepared from a modified resin, wherein the modified resin is treated with potassium carbonate using 4-maleimidophenol as a raw material, and then reacted with 3-chloropropyltriethoxysilane, so that the hydroxyl group on the 4-maleimidophenol reacts with the chlorine atom site on the 3-chloropropyltriethoxysilane to obtain a modifier, and a carboxyl carbon nanotube is reacted with KH550, so that the carboxyl group on the carboxyl carbon nanotube reacts with the amino group on the KH550 to obtain a pre-treated The method comprises the following steps: treating carbon nanotubes, hydrolyzing and condensing the pretreated carbon nanotubes, KH550 and the modifier, forming a silicone-coated carbon nanotube with amino and maleimide groups on the surface thereof, reacting the modified carbon nanotubes with 4-formylphenylboronic acid, reducing the activity of the boronic acid group under the action of n-hexane, causing the amino group on the modified carbon nanotube to react with the aldehyde group on the 4-formylphenylboronic acid, and obtaining functionalized carbon nanotubes; reacting the reinforcing filler, the functionalized carbon nanotubes with 1,4-phenylenediboronic acid, causing the boronic acid groups to be grafted with each other, and obtaining a composite filler; reacting the SBS masterbatch, the PP masterbatch, the composite filler and diisopropylbenzene peroxide, causing the double bonds in the composite filler to be grafted with the molecular chains of the SBS masterbatch and the PP masterbatch, and obtaining a modified resin.
[0014] The reinforcing filler is prepared by ring-opening octamethylcyclotetrasiloxane and tetramethylcyclotetrasiloxane as raw materials, and then polymerizing with 1,3-bis(aminopropyl)tetramethyldisiloxane to obtain bisaminopolysiloxane, reacting the bisaminopolysiloxane with 4-vinylbenzaldehyde so that the amino group on the bisaminopolysiloxane reacts with the aldehyde group on the 4-vinylbenzaldehyde to obtain a modified monomer, polymerizing styrene, acrylonitrile and the modified monomer to form a polymer on the surface of polytetrafluoroethylene to form a core-shell structure to obtain a precursor, reacting the precursor with DOPO so that the C=N bond on the surface of the precursor reacts with the PH bond on the DOPO to obtain a modified precursor, reacting the modified precursor with 4-vinylbenzeneboronic acid so that the Si-H bond on the modified precursor reacts with the double bond on the 4-vinylbenzeneboronic acid to obtain a reinforcing filler.
[0015] When the cable burns, the polytetrafluoroethylene in the composite filler decomposes to produce free radicals. These free radicals can react with oxygen in the air to form a dense fluoride protective film on the cable surface, thereby isolating oxygen and flames. The organic phosphorus on the surface will decompose when heated to produce substances such as phosphoric acid, metaphosphoric acid and polymetaphosphoric acid. These substances have strong dehydration properties and can dehydrate and carbonize the polymer surface. They can form a dense silicon-nitrogen layer when compounded with the organic silicon structure. The doping with boron and nitrogen elements further improves the density of the silicon-carbon layer, forming a multi-layer protective layer on the cable surface, effectively avoiding the generation of dripping materials. At the same time, carbon nanotubes can form a network structure, which can block the transfer of oxygen and heat and improve the flame retardant effect. DETAILED DESCRIPTION
[0016] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] Embodiment 1: A highly flame-retardant insulated power cable, comprising a plurality of conductors arranged in sequence from the inside to the outside, wherein the surface of the conductor is coated with an insulating layer, a wrapped inner lining layer is arranged outside the insulating layer, a filler is filled between the wrapped inner lining layer and the insulating layer, a protective layer is coated outside the wrapped inner lining layer, and a sheath is coated outside the protective layer; The conductor is a tinned copper wire, the inner lining layer of the wrapping is a mica tape, the filler is glass fiber, the insulation layer and the protective layer are polyvinyl chloride, the model of the polyvinyl chloride is SG-1, and the sheath is prepared from modified resin.
[0018] The modified resin is prepared by the following steps: Step A1: 4-maleimidophenol, potassium carbonate and DMF were mixed evenly, nitrogen was introduced for protection, and the reaction was carried out for 10 minutes at a speed of 120 r / min and a temperature of 50° C., and then 3-chloropropyltriethoxysilane was added and reacted for 1 hour to obtain a modifier, and carboxyl carbon nanotubes, dicyclohexylcarbodiimide, KH550 and toluene were mixed evenly, and the reaction was carried out for 3 hours at a speed of 200 r / min and a temperature of 20° C. to obtain pretreated carbon nanotubes; Step A2: Dispersing the pretreated carbon nanotubes in ethanol, stirring and adding KH550, a modifier and deionized water at a speed of 200 r / min and a temperature of 60° C., reacting for 3 h to obtain modified carbon nanotubes, and uniformly mixing the modified carbon nanotubes, 4-formylphenylboronic acid and n-hexane, reacting for 5 min at a speed of 60 r / min and a temperature of 70° C. to obtain functionalized carbon nanotubes; Step A3: The reinforcing filler, functionalized carbon nanotubes, 1,4-phenylenediboric acid and toluene are mixed, stirred for 6 hours at a speed of 600 r / min and a temperature of 70°C to obtain a composite filler, and the SBS masterbatch, PP masterbatch, composite filler, diisopropylbenzene peroxide and xylene are mixed evenly, reacted for 2 hours at a speed of 60 r / min and a temperature of 130°C, cooled to room temperature, the filtrate is filtered to remove the filtrate, and the filter cake is melt-extruded to obtain a modified resin.
[0019] The molar ratio of 4-maleimidophenol, potassium carbonate and 3-chloropropyltriethoxysilane in step A1 is 1:1.1:1, and the molar ratio of carboxyl groups on carboxyl carbon nanotubes, dicyclohexylcarbodiimide and KH550 is 1:1:1.
[0020] The amount ratio of the pretreated carbon nanotubes, ethanol, KH550, modifier and deionized water described in step A2 is 1g:15mL:30mg:30mg:3mL, and the molar ratio of the amino groups on the modified carbon nanotubes to 4-formylphenylboronic acid is 1:1.
[0021] The mass ratio of the reinforcing filler, functionalized carbon nanotubes and 1,4-phenylenediboric acid described in step A3 is 1:3:3, the weight ratio of SBS masterbatch, PP masterbatch, composite filler and dicumyl peroxide is 40:130:35:3, the SBS masterbatch model is YH792, and the PP masterbatch model is K8003.
[0022] The reinforcing filler is prepared by the following steps: Step B1: octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(aminopropyl)tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the mixture is reacted for 3 hours at a speed of 120 r / min and a temperature of 105° C. to obtain bisaminopolysiloxane; bisaminopolysiloxane, 4-vinylbenzaldehyde, sodium carbonate and DMF are mixed uniformly, and the mixture is reacted for 5 hours at a speed of 150 r / min and a temperature of 80° C. to obtain a modified monomer; Step B2: Sodium dodecylbenzene sulfonate, styrene, acrylonitrile, modified monomer and DMF are mixed uniformly, and potassium persulfate and polytetrafluoroethylene emulsion are added under the conditions of a rotation speed of 200 r / min and a temperature of 80° C., and the reaction is carried out for 2 hours, and the temperature is raised to 90° C. and the reaction is continued for 3 hours to obtain a composite liquid, and the composite liquid and sulfuric acid solution are mixed uniformly, and sulfuric acid solution is added under the conditions of a rotation speed of 600 r / min and a temperature of 90° C., and the mixture is stirred for 1 hour, and the filtrate is filtered to remove the filtrate to obtain a precursor; Step B3: The precursor, DOPO and ethanol are mixed evenly, and refluxed for reaction at a speed of 60 r / min and a temperature of 78°C for 3 hours to obtain a modified precursor; the modified precursor, 4-vinylbenzeneboric acid, chloroplatinic acid and n-hexane are mixed evenly, and reacted at a speed of 120 r / min and a temperature of 80°C for 2 hours to obtain a reinforced filler.
[0023] The molar ratio of octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(aminopropyl)tetramethyldisiloxane described in step B1 is 1.4:1:3:2, the molar ratio of bisaminopolysiloxane and 4-vinylbenzaldehyde is 1:2, and the amount of sodium carbonate used is 1% by mass of 4-vinylbenzaldehyde.
[0024] The mass ratio of sodium dodecylbenzene sulfonate, styrene, acrylonitrile, modified monomer and DMF, potassium persulfate and polytetrafluoroethylene emulsion described in step B2 is 0.8:45:12:15:200:0.3:20, the solid content of polytetrafluoroethylene emulsion is 60%, the mass ratio of the composite liquid and sulfuric acid solution is 2:5, and the mass fraction of sulfuric acid solution is 5%.
[0025] The amount ratio of the precursor, DOPO and ethanol described in step B3 is 1g:1.5g:15mL, the molar ratio of the Si-H bond on the modified precursor and 4-vinylbenzeneboronic acid is 1:1, and the amount of chloroplatinic acid is 1‰ of the mass of 4-vinylbenzeneboronic acid.
[0026] Embodiment 2: A highly flame-retardant insulated power cable, comprising a plurality of conductors arranged in sequence from the inside to the outside, wherein the surface of the conductor is coated with an insulating layer, a wrapped inner lining layer is arranged outside the insulating layer, a filler is filled between the wrapped inner lining layer and the insulating layer, a protective layer is coated outside the wrapped inner lining layer, and a sheath is coated outside the protective layer; The conductor is a tinned copper wire, the inner lining layer of the wrapping is a mica tape, the filler is glass fiber, the insulation layer and the protective layer are polyvinyl chloride, the model of the polyvinyl chloride is SG-1, and the sheath is prepared from modified resin.
[0027] The modified resin is prepared by the following steps: Step A1: 4-maleimidophenol, potassium carbonate and DMF were mixed evenly, nitrogen was introduced for protection, and the reaction was carried out for 15 minutes at a speed of 120 r / min and a temperature of 55° C., and then 3-chloropropyltriethoxysilane was added and reacted for 1.5 hours to obtain a modifier, and carboxyl carbon nanotubes, dicyclohexylcarbodiimide, KH550 and toluene were mixed evenly, and the reaction was carried out for 4 hours at a speed of 200 r / min and a temperature of 25° C. to obtain pretreated carbon nanotubes; Step A2: Dispersing the pretreated carbon nanotubes in ethanol, stirring and adding KH550, a modifier and deionized water at a speed of 200 r / min and a temperature of 65° C., reacting for 4 hours to obtain modified carbon nanotubes, and uniformly mixing the modified carbon nanotubes, 4-formylphenylboric acid, sodium carbonate and n-hexane, reacting for 10 minutes at a speed of 60 r / min and a temperature of 75° C. to obtain functionalized carbon nanotubes; Step A3: The reinforcing filler, functionalized carbon nanotubes, 1,4-phenylenediboric acid and toluene are mixed, stirred for 7 hours at a speed of 600 r / min and a temperature of 75°C to obtain a composite filler, and the SBS masterbatch, PP masterbatch, composite filler, diisopropylbenzene peroxide and xylene are mixed evenly, reacted for 2.5 hours at a speed of 60 r / min and a temperature of 130°C, cooled to room temperature, the filtrate is filtered to remove the filtrate, and the filter cake is melt-extruded to obtain a modified resin.
[0028] The molar ratio of 4-maleimidophenol, potassium carbonate and 3-chloropropyltriethoxysilane in step A1 is 1:1.1:1, and the molar ratio of carboxyl groups on carboxyl carbon nanotubes, dicyclohexylcarbodiimide and KH550 is 1:1:1.
[0029] The amount ratio of the pretreated carbon nanotubes, ethanol, KH550, modifier and deionized water described in step A2 is 1g:15mL:30mg:30mg:3mL, and the molar ratio of the amino groups on the modified carbon nanotubes to 4-formylphenylboronic acid is 1:1.
[0030] The mass ratio of the reinforcing filler, functionalized carbon nanotubes and 1,4-phenylenediboric acid described in step A3 is 1:3:3, the weight ratio of SBS masterbatch, PP masterbatch, composite filler and dicumyl peroxide is 50:140:45:5, the SBS masterbatch model is YH792, and the PP masterbatch model is K8003.
[0031] The reinforcing filler is prepared by the following steps: Step B1: octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(aminopropyl)tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the mixture is reacted for 4 hours at a speed of 120 r / min and a temperature of 110° C. to obtain bisaminopolysiloxane; bisaminopolysiloxane, 4-vinylbenzaldehyde, sodium carbonate and DMF are mixed uniformly, and the mixture is reacted for 6 hours at a speed of 200 r / min and a temperature of 80° C. to obtain a modified monomer; Step B2: Sodium dodecylbenzene sulfonate, styrene, acrylonitrile, modified monomer and DMF are mixed uniformly, and potassium persulfate and polytetrafluoroethylene emulsion are added under the conditions of a rotation speed of 200 r / min and a temperature of 85° C., and the reaction is carried out for 2 hours, and the temperature is raised to 95° C. and the reaction is continued for 4 hours to obtain a composite liquid, and the composite liquid and sulfuric acid solution are mixed uniformly, and sulfuric acid solution is added under the conditions of a rotation speed of 600 r / min and a temperature of 95° C., and the mixture is stirred for 1 hour, and the filtrate is filtered to remove the filtrate to obtain a precursor; Step B3: The precursor, DOPO and ethanol are mixed evenly, and refluxed for reaction at a speed of 80 r / min and a temperature of 78°C for 5 hours to obtain a modified precursor. The modified precursor, 4-vinylbenzeneboric acid, chloroplatinic acid and n-hexane are mixed evenly, and reacted at a speed of 120 r / min and a temperature of 85°C for 3 hours to obtain a reinforced filler.
[0032] The molar ratio of octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(aminopropyl)tetramethyldisiloxane described in step B1 is 1.4:1:3:2, the molar ratio of bisaminopolysiloxane and 4-vinylbenzaldehyde is 1:2, and the amount of sodium carbonate used is 1% by mass of 4-vinylbenzaldehyde.
[0033] The mass ratio of sodium dodecylbenzene sulfonate, styrene, acrylonitrile, modified monomer and DMF, potassium persulfate and polytetrafluoroethylene emulsion described in step B2 is 0.8:45:12:15:200:0.3:20, the solid content of polytetrafluoroethylene emulsion is 60%, the mass ratio of the composite liquid and sulfuric acid solution is 2:5, and the mass fraction of sulfuric acid solution is 5%.
[0034] The amount ratio of the precursor, DOPO and ethanol described in step B3 is 1g:1.5g:15mL, the molar ratio of the Si-H bond on the modified precursor and 4-vinylbenzeneboronic acid is 1:1, and the amount of chloroplatinic acid is 1‰ of the mass of 4-vinylbenzeneboronic acid.
[0035] Embodiment 3: A highly flame-retardant insulated power cable, comprising a plurality of conductors arranged in sequence from the inside to the outside, wherein the surface of the conductor is coated with an insulating layer, a wrapped inner lining layer is arranged outside the insulating layer, a filler is filled between the wrapped inner lining layer and the insulating layer, a protective layer is coated outside the wrapped inner lining layer, and a sheath is coated outside the protective layer; The conductor is a tinned copper wire, the inner lining layer of the wrapping is a mica tape, the filler is glass fiber, the insulation layer and the protective layer are polyvinyl chloride, the model of the polyvinyl chloride is SG-1, and the sheath is prepared from modified resin.
[0036] The modified resin is prepared by the following steps: Step A1: 4-maleimidophenol, potassium carbonate and DMF were mixed evenly, nitrogen was introduced for protection, and the reaction was carried out for 15 minutes at a speed of 150 r / min and a temperature of 60° C., and then 3-chloropropyltriethoxysilane was added and reacted for 1.5 hours to obtain a modifier, and carboxyl carbon nanotubes, dicyclohexylcarbodiimide, KH550 and toluene were mixed evenly, and the reaction was carried out for 5 hours at a speed of 300 r / min and a temperature of 25° C. to obtain pretreated carbon nanotubes; Step A2: Dispersing the pretreated carbon nanotubes in ethanol, stirring and adding KH550, a modifier and deionized water at a speed of 300 r / min and a temperature of 70°C, reacting for 5 hours to obtain modified carbon nanotubes, and uniformly mixing the modified carbon nanotubes, 4-formylphenylboric acid, sodium carbonate and n-hexane, reacting for 10 minutes at a speed of 80 r / min and a temperature of 75°C to obtain functionalized carbon nanotubes; Step A3: The reinforcing filler, functionalized carbon nanotubes, 1,4-phenylenediboric acid and toluene are mixed, stirred for 8 hours at a speed of 800 r / min and a temperature of 80°C to obtain a composite filler, and the SBS masterbatch, PP masterbatch, composite filler, diisopropylbenzene peroxide and xylene are mixed evenly, reacted for 2.5 hours at a speed of 80 r / min and a temperature of 135°C, cooled to room temperature, the filtrate is filtered to remove the filtrate, and the filter cake is melt-extruded to obtain a modified resin.
[0037] The molar ratio of 4-maleimidophenol, potassium carbonate and 3-chloropropyltriethoxysilane in step A1 is 1:1.1:1, and the molar ratio of carboxyl groups on carboxyl carbon nanotubes, dicyclohexylcarbodiimide and KH550 is 1:1:1.
[0038] The amount ratio of the pretreated carbon nanotubes, ethanol, KH550, modifier and deionized water described in step A2 is 1g:15mL:30mg:30mg:3mL, and the molar ratio of the amino groups on the modified carbon nanotubes to 4-formylphenylboronic acid is 1:1.
[0039] The mass ratio of the reinforcing filler, functionalized carbon nanotubes and 1,4-phenylenediboric acid described in step A3 is 1:3:3, the weight ratio of SBS masterbatch, PP masterbatch, composite filler and dicumyl peroxide is 60:150:55:8, the SBS masterbatch model is YH792, and the PP masterbatch model is K8003.
[0040] The reinforcing filler is prepared by the following steps: Step B1: octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(aminopropyl)tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the mixture is reacted for 5 hours at a speed of 150 r / min and a temperature of 110° C. to obtain bisaminopolysiloxane; bisaminopolysiloxane, 4-vinylbenzaldehyde, sodium carbonate and DMF are mixed uniformly, and the mixture is reacted for 7 hours at a speed of 200 r / min and a temperature of 90° C. to obtain a modified monomer; Step B2: Sodium dodecylbenzene sulfonate, styrene, acrylonitrile, modified monomer and DMF are mixed uniformly, and potassium persulfate and polytetrafluoroethylene emulsion are added under the conditions of a rotation speed of 300 r / min and a temperature of 85° C., and the reaction is carried out for 3 hours, and the temperature is raised to 95° C. and the reaction is continued for 5 hours to obtain a composite liquid, and the composite liquid and sulfuric acid solution are mixed uniformly, and sulfuric acid solution is added under the conditions of a rotation speed of 800 r / min and a temperature of 95° C., and the mixture is stirred for 1.5 hours, and the filtrate is filtered to remove the filtrate to obtain a precursor; Step B3: The precursor, DOPO and ethanol are mixed evenly, and refluxed for reaction at a speed of 80 r / min and a temperature of 80°C for 5 hours to obtain a modified precursor. The modified precursor, 4-vinylbenzeneboric acid, chloroplatinic acid and n-hexane are mixed evenly, and reacted at a speed of 150 r / min and a temperature of 85°C for 4 hours to obtain a reinforced filler.
[0041] The molar ratio of octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(aminopropyl)tetramethyldisiloxane described in step B1 is 1.4:1:3:2, the molar ratio of bisaminopolysiloxane and 4-vinylbenzaldehyde is 1:2, and the amount of sodium carbonate used is 1% by mass of 4-vinylbenzaldehyde.
[0042] The mass ratio of sodium dodecylbenzene sulfonate, styrene, acrylonitrile, modified monomer and DMF, potassium persulfate and polytetrafluoroethylene emulsion described in step B2 is 0.8:45:12:15:200:0.3:20, the solid content of polytetrafluoroethylene emulsion is 60%, the mass ratio of the composite liquid and sulfuric acid solution is 2:5, and the mass fraction of sulfuric acid solution is 5%.
[0043] The amount ratio of the precursor, DOPO and ethanol described in step B3 is 1g:1.5g:15mL, the molar ratio of the Si-H bond on the modified precursor and 4-vinylbenzeneboronic acid is 1:1, and the amount of chloroplatinic acid is 1‰ of the mass of 4-vinylbenzeneboronic acid.
[0044] Comparative Example 1: Compared with Example 1, no reinforcing filler was added in this comparative example, and the remaining steps were the same.
[0045] Comparative Example 2: Compared with Example 1, no functionalized carbon nanotubes were added in this comparative example, and the remaining steps were the same.
[0046] Comparative Example 3. Compared with Example 1, sodium dodecylbenzene sulfonate, styrene, acrylonitrile and DMF were mixed evenly, and potassium persulfate and polytetrafluoroethylene emulsion were added under the conditions of a rotation speed of 200 r / min and a temperature of 80°C, and the reaction was carried out for 2 hours. The temperature was raised to 90°C and the reaction was continued for 3 hours to obtain a composite liquid. The composite liquid and sulfuric acid solution were mixed evenly, and the sulfuric acid solution was added under the conditions of a rotation speed of 600 r / min and a temperature of 90°C. The mixture was stirred for 1 hour, and the filtrate was filtered to remove the filtrate. The obtained product replaced the reinforcing filler, and the remaining steps were the same.
[0047] The modified resins obtained in Examples 1-3 and Comparative Examples 1-3 were used to prepare 130 mm × 13 mm × 4 mm samples according to the standard of GB / T2408-2021, and the vertical combustion level and flame extinction time were tested. The test results are shown in Table 1 below; Table 1
[0048] It can be seen from Table 1 above that the present invention has a very good flame retardant effect.
[0049] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. High flame retardant insulation power cable, characterized by: It includes a plurality of conductors arranged in sequence from the inside to the outside, the surface of the conductor is coated with an insulating layer, a wrapped inner lining layer is arranged outside the insulating layer, a filler is filled between the wrapped inner lining layer and the insulating layer, a protective layer is coated outside the wrapped inner lining layer, and a sheath is coated outside the protective layer; The conductor is a tinned copper wire, the inner lining layer of the wrapping is a mica tape, the filler is glass fiber yarn, the insulating layer and the protective layer are polyvinyl chloride, and the sheath is prepared from modified resin.
2. The highly flame-retardant insulated power cable according to claim 1, characterized in that: The modified resin is prepared by the following steps: Step A1: 4-maleimidophenol, potassium carbonate and DMF are mixed evenly, nitrogen is introduced for protection, and after the reaction, 3-chloropropyltriethoxysilane is added and the reaction is carried out for 1-1.5 hours to obtain a modifier, and carboxyl carbon nanotubes, dicyclohexylcarbodiimide, KH550 and toluene are mixed and reacted to obtain pretreated carbon nanotubes; Step A2: dispersing the pretreated carbon nanotubes in ethanol, stirring and adding KH550, a modifier and deionized water to react to obtain modified carbon nanotubes, and mixing the modified carbon nanotubes, 4-formylphenylboric acid, sodium carbonate and n-hexane to react to obtain functionalized carbon nanotubes; Step A3: The reinforcing filler, the functionalized carbon nanotubes, 1,4-phenylenediboric acid and toluene are mixed and stirred to obtain a composite filler, the SBS masterbatch, the PP masterbatch, the composite filler, diisopropylbenzene peroxide and xylene are mixed and reacted, the temperature is lowered to room temperature, the filtrate is filtered to remove the filtrate, and the filter cake is melt-extruded to obtain a modified resin.
3. The highly flame-retardant insulated power cable according to claim 2, characterized in that: The molar ratio of 4-maleimidophenol, potassium carbonate and 3-chloropropyltriethoxysilane in step A1 is 1:1.1:1, and the molar ratio of carboxyl groups on carboxyl carbon nanotubes, dicyclohexylcarbodiimide and KH550 is 1:1:
1.
4. The highly flame-retardant insulated power cable according to claim 2, characterized in that: The amount ratio of the pretreated carbon nanotubes, ethanol, KH550, modifier and deionized water described in step A2 is 1g:15mL:30mg:30mg:3mL, and the molar ratio of the amino groups on the modified carbon nanotubes to 4-formylphenylboronic acid is 1:
1.
5. The highly flame-retardant insulated power cable according to claim 2, characterized in that: The mass ratio of the reinforcing filler, functionalized carbon nanotubes and 1,4-phenylenediboric acid described in step A3 is 1:3:3, and the weight ratio of SBS masterbatch, PP masterbatch, composite filler and dicumyl peroxide is 40-60:130-150:35-55:3-8.
6. The highly flame-retardant insulated power cable according to claim 2, characterized in that: The reinforcing filler is prepared by the following steps: Step B1: octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(aminopropyl)tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the mixture is reacted to obtain bisaminopolysiloxane, and the bisaminopolysiloxane, 4-vinylbenzaldehyde, sodium carbonate and DMF are mixed for reaction to obtain a modified monomer; Step B2: Sodium dodecylbenzene sulfonate, styrene, acrylonitrile, a modified monomer and DMF are mixed and stirred, and potassium persulfate and polytetrafluoroethylene emulsion are added to react to obtain a composite liquid, the composite liquid and sulfuric acid solution are mixed and stirred, and sulfuric acid solution is added, stirred, and the filtrate is filtered to remove the filtrate to obtain a precursor; Step B3: The precursor, DOPO and ethanol are mixed and refluxed to obtain a modified precursor, and the modified precursor, 4-vinylbenzeneboronic acid, chloroplatinic acid and n-hexane are mixed and reacted to obtain a reinforced filler.
7. The highly flame-retardant insulated power cable according to claim 6, characterized in that: The molar ratio of octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(aminopropyl)tetramethyldisiloxane described in step B1 is 1.4:1:3:2, and the molar ratio of bisaminopolysiloxane and 4-vinylbenzaldehyde is 1:
2.
8. The highly flame-retardant insulated power cable according to claim 6, characterized in that: The mass ratio of sodium dodecylbenzene sulfonate, styrene, acrylonitrile, modified monomer and DMF, potassium persulfate and polytetrafluoroethylene emulsion described in step B2 is 0.8:45:12:15:200:0.3:20, and the mass ratio of the composite liquid and sulfuric acid solution is 2:
5.
9. The highly flame-retardant insulated power cable according to claim 6, characterized in that: The amount ratio of the precursor, DOPO and ethanol described in step B3 is 1 g:1.5 g:15 mL, and the molar ratio of the Si-H bond on the modified precursor and 4-vinylbenzene boronic acid is 1:1.
Citation Information
Patent Citations
Flame-retardant cable
CN118374095A
Rod-control and rod-position combined instrument-control cable for nuclear power plant reactor
CN120518945A
Electric cable
WO2012127786A1
Flame-retardant masterbatch, preparation method therefor, and application thereof
WO2021243836A1
Cited By
High-heat-resistance electronic connecting wire and preparation method thereof
CN120545029A